Direct oral anticoagulants for the treatment of cerebral venous thrombosis – a protocol of an international phase IV study - van de Munckhof, Anita; Sánchez van Kammen, Mayte; Krzywicka, Katarzyna; Aaron, Sanjith; Aguiar de Sousa, Diana; Antochi, Florina; Arauz, Antonio; Barboza, Miguel A.; Conforto, Adriana B.; Dentali, Francesco; Galdames Contreras, Daniel; Ji, Xunming; et al. (Frontiers in Neurology, 2023)
Introduction Current guidelines recommend that patients with cerebral venous thrombosis (CVT) should be treated with vitamin K antagonists (VKAs) for 3–12 months. Direct oral anticoagulants (DOACs), however, are increasingly used in clinical practice. An exploratory randomized controlled trial including 120 patients with CVT suggested that the efficacy and safety profile of dabigatran (a DOAC) is similar to VKAs for the treatment of CVT, but large-scale prospective studies from a real-world setting are lacking. Methods DOAC-CVT is an international, prospective, observational cohort study comparing DOACs to VKAs for the prevention of recurrent venous thrombotic events after acute CVT. Patients are eligible if they are 18 years or older, have a radiologically confirmed CVT, and have started oral anticoagulant treatment (DOAC or VKA) within 30 days of CVT diagnosis. Patients with an absolute contra-indication for DOACs, such as pregnancy or severe renal insufficiency, are excluded from the study. We aim to recruit at least 500 patients within a three-year recruitment period. The primary endpoint is a composite of recurrent venous thrombosis and major bleeding at 6 months of follow-up. We will calculate an adjusted odds ratio for the primary endpoint using propensity score inverse probability treatment weighting. Discussion DOAC-CVT will provide real-world data on the comparative efficacy and safety of DOACs versus VKAs for the treatment of CVT. Clinical trial registration ClinicalTrials.gov, NCT04660747.